2017
DOI: 10.1038/s41467-017-01309-6
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3H structure reveals an unusual mechanism of interaction with duplex RNA

Abstract: The APOBEC3 family of cytidine deaminases cause lethal hypermutation of retroviruses via deamination of newly reverse-transcribed viral DNA. Their ability to bind RNA is essential for virion infiltration and antiviral activity, yet the mechanisms of viral RNA recognition are unknown. By screening naturally occurring, polymorphic, non-human primate APOBEC3H variants for biological and crystallization properties, we obtained a 2.24-Å crystal structure of pig-tailed macaque APOBEC3H with bound RNA. Here, we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
119
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(138 citation statements)
references
References 57 publications
16
119
1
1
Order By: Relevance
“…Since A3H and A3A are singledomain enzymes with nearly identical cores, we constructed additional chimeras to ask what surface residues are required to endow A3A with A3H properties. We first tested other components of the RNA binding interface because our work implicated loop 1 in nucleolar retention (see above) and structural studies showed select loop 1 residues together with loop 7 or ␣-helix 6 residues combining to bind duplex RNA (40,41,48). We therefore generated A3A chimeras that exchanged loop 7 or ␣-helix 6 alone or in combination with loop 1 and assessed localization (structural overlay in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since A3H and A3A are singledomain enzymes with nearly identical cores, we constructed additional chimeras to ask what surface residues are required to endow A3A with A3H properties. We first tested other components of the RNA binding interface because our work implicated loop 1 in nucleolar retention (see above) and structural studies showed select loop 1 residues together with loop 7 or ␣-helix 6 residues combining to bind duplex RNA (40,41,48). We therefore generated A3A chimeras that exchanged loop 7 or ␣-helix 6 alone or in combination with loop 1 and assessed localization (structural overlay in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, interactions between several A3s and cellular proteins can be disrupted by RNase A treatment, suggesting that RNA plays a pivotal role in regulating A3 activities. This is further evidenced by recent studies requiring RNase A treatment in order to purify high quantities of recombinant A3H protein from cell lysates (40,41,48).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The first ever A3H structure was recently published of a macaque A3H (macA3H) bound to dsRNA [Fig. (e)] . This was also the first structure of an APOBEC bound to RNA, albeit of unknown sequence (resolution was not high enough to identify the nucleotides of copurified RNA).…”
Section: Introductionmentioning
confidence: 88%
“…The activity of A3H is improved through its ability to oligomerize, dimerization is uniquely mediated through an RNA intermediate [130][131][132]. Interestingly, two studies recently identified that A3H may be able to dimerize through an RNA mediated mechanism that involves loops 1 and 7 as well as helix 6 and that the presence of bound RNA alters the activity of the A3H [131,133]. These findings warrant future work on the exact nature of A3H oligomerization and activity.…”
Section: Deamination-dependent Restriction Of Hiv By A3hmentioning
confidence: 95%